Chronic medication in a patient list (Portuguese Journal of Family Medicine and General Practice, 2000)
Polymedication is undoubtedly one of the most important problems with which family doctors have to deal. Objectives: To characterise the the chronic medication consuming patients of a family doctors patient list in terms of age, gender, type of family, and number and kind of medications used. Study type: This was a descriptive, cross-sectional study. Site: Olivais Norte Health Unit, Olivais Health Centre. Population: All attending chronically-medicated patients who belonged to one family doctors list. Methods: Of a total of 1,543 patients from a family doctors list, 887 were current attenders, and 346 chronically-medicated patients were studied. The age, gender and type of family variables were studied in relation with the number and type of medications used. This study took place in June and July 1994. Results and Conclusions: Women, the elderly, and singleelement families were those who consumed the greater number of medications. Each chronic medication user took on average 2.38 medications, with no relevant differences between sexes. The widest gap in medication use between sexes was found in the 15 to 44 year age group, for which the most used medication type was that of oral contraceptives, whereas above 45 years it was that of anti-hypertensives. It is important that family doctors be more aware of their patients medication habits, which is essential if one is to decrease the harmful effects of excessive medication use.
Keywords: Medication; Polymedication; Chronic Patients